(untitled) (Comparative Professional Pedagogy, 2023)
The article discloses the concept and procedure of monitoring the quality of professional competence of teaching staff of higher education institutions, which is a holistic management tool for storing, processing and disseminating information on the quality of professional activity of teachers of higher education, determining its state of development and forecasting in the context of developing the methodology for its implementation. It is noted that the monitoring is stipulated by the motivation the specific feature of which is that the teacher is interested in objective and independent evaluation of their work, finding new technologies, determining the path of their own professional growth, attending open classes of colleagues and taking courses to improve professional qualifications. The "factor-criterion submodel of the professional activity of a teacher of higher educational institutions" is presented. Its parameters are the development of the professional competence of teachers as the quality of their activity and the level of their activities organization. The listed factors are in the compliance with the criteria selected according to a logical analysis of the organization of the professional activity of teaching staff and compliance with regulatory documents of higher education institutions. The organization of monitoring regarding the determination of the diagnosis of pedagogical activity and the analysis of the effectiveness of the expected indicators of the quality of education according to the specified indicators serves as an effective factor in the professional growth of the teacher. Monitoring requires a functional division of duties (action algorithm) according to the organizational procedure. The classification according to the monitoring evaluation procedure is presented according to the five levels of the higher education quality assurance system. Monitoring the satisfaction with the professional activity of teachers of higher education institutions in the context of the provision and implementation of the developed factor-criterion model allows to monitor the dynamics of indicators regarding the satisfaction of the staff with the effectiveness of their own obtained results, which contribute to the improvement of the quality of the professional education of teachers.